1988
DOI: 10.1159/000263339
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Cerebral Asphyxia: Pharmacological Intervention

Abstract: Perinatal asphyxia is associated with an increased risk of cerebral palsy and significant mortality. We investigated the use of flunarizine, a calcium antagonist and MK-801, an excitatory amino acid antagonist, in preventing the sequelae of severe hypoxic/ischemic insults. Flunarizine was neuroprotective in the infant rat subjected to unilateral carotid ligation and 2 h of hypoxia. Preliminary analysis of experiments in a novel model of cerebral ischemia in the fetal sheep suggests that prophylactic treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the beneficial effects of antagonists directed towards glutamate receptors. For instance, pretreatment with the N MDA‐receptor antagonist MK801 in the rat 89–91 , and in catheterised fetal sheep 92 affords marked neuroprotection. In P7 rats subjected to unilateral carotid artery ligation followed by 2 h of hypoxia (7.7% oxygen), treatment with the N MDA antagonist kyneuronic acid resulted in the volume of cerebral infarction being reduced by one‐ third (from 38 to 25%) 93 .…”
Section: Prominent Hypothesesmentioning
confidence: 99%
“…Several studies have demonstrated the beneficial effects of antagonists directed towards glutamate receptors. For instance, pretreatment with the N MDA‐receptor antagonist MK801 in the rat 89–91 , and in catheterised fetal sheep 92 affords marked neuroprotection. In P7 rats subjected to unilateral carotid artery ligation followed by 2 h of hypoxia (7.7% oxygen), treatment with the N MDA antagonist kyneuronic acid resulted in the volume of cerebral infarction being reduced by one‐ third (from 38 to 25%) 93 .…”
Section: Prominent Hypothesesmentioning
confidence: 99%